Perjuangan Pasraman Formal agar tetap Eksis sebagai Lembaga Pendidikan di Bali - I Made Bagus Andi Purnomo (Jurnal Kajian Bali (Journal of Bali Studies), 2023)
The existence of formal pasraman (a specific educational institution based on Hinduism) was firstly welcomed warmly by Balinese people. Nevertheless, this existence is being destabilized because the existing formal pasraman experiences several limitations on fulfillment of educational standard requirements. This research observes the challenges of formal pasraman in Bali to subsist as a formal educational institution. Applying qualitative approach, this research collected data through observation, interview, and document study techniques. Data were analyzed eclectically using three theories, namely hegemony theory, structural functionalism, and innovation diffusion. This research discovered diverse obstructions faced by formal pasraman with the aim of continuing to subsist as a formal educational institution, mainly having been the struggle of formal pasraman to be registered in Basic Education Data (Dapodik) and to be broadly acknowledged by the people of Bali.